ROOT CONDITION OF PINE AND BIRCH IN AREAS AFFECTED BY ROOT ROT CAUSED BY HETEROBASIDION ANNOSUM (FR.) BREF. - Ustsky, I. M.; Vedmid, M. M.; Mihaylichenko, O. A. (Forestry and Forest Melioration, 2018)
IntroductionOne of the important points of the existing recommendations on control of the root rot caused by Heterobasidion annosum (Fr.) Bref. is to create birch and other deciduous plantations for reclamative afforestation in fresh and moist relatively poor forest site conditions as preceding crops for Scots pine (Pinus sylvestris L.) plantations. It is necessary to reduce infection background of Heterobasidion annosum and to promote protection of soil microbiota. Silver birch (Betula pendula Roth.), as the main associate species of pine, can also be affected by Heterobasidion annosum. However, the possibility for root rot foci development in birch stands created on former arable lands remains a contentious issue. The aim of our research was to reveal the peculiarities of pine and birch root systems in pure and mixed stands of the first generation on the former agricultural (former arable) lands in the focus of root rot – Heterobasidion annosum (Fr.) Bref. Materials and MethodsResearch was carried out in birch and pine stands of the first generation planted on former arable lands in the State Forest Enterprises of Chernihiv Polissya. The condition of root systems in plantations affected and unaffected by Heterobasidion annosum was estimated by identifying the status of all visible roots (healthy, infected, dead) and by measuring their diameters on the wall of the excavated pits (1.0 ? 0.3 m). The pits were located on the west and east sides at a distance of 0.5 m from stem perpendicularly to its center. The presence of Heterobasidion annosum root rot was determined using method of moist chambers which were made in excavated pits. Fruiting bodies formed after 4 months were accounted.Results and Conclusions It is noted that root length gradually reduced under the influence of root rot. Sum of roots sectional areas of pine of different condition increases from V to IX age classes in 3.4 times. The proportion of healthy roots for healthy and relatively healthy pine trees in the plantations affected by Heterobasidion annosum ranges from 76 to 97%. In conditions of wet pits cameras, individual fruiting bodies of the pathogen formed on healthy – by external features – roots of pine trees while for the trees of III and IV condition category their appearance was massive. For the birch stands of age class V, no significant difference was observed between the sum of the cross-sectional areas of the roots in fresh infertile and fairly infertile pine site conditions. Fruiting bodies of Heterobasidion annosum on the roots of birch were smaller and formed in the small-diameter roots. There is a massive reproduction of the mycelium of saprophytic fungi in the pure cultures of birch trees on old arable lands, but the plantations affection by Armillaria mellea (Vahl. ex Fr.) Kummer is possible, and, in case of root contacts with the pine tree, the Heterobasidion annosum also. In fresh dead standing trees of both pine and birch all the roots were dead.